Penerapan Teori Condito Sine Qua Non dalam Prinsip Apologetika Kristen - John Abraham Christiaan; Didit Yuliantono Adi; Tri Hananto; Stefanus Dully; Jerimias Manuhutu (CHARISTHEO: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
The idea of writing about this topic originated from observations on social media that several Christian apologists were entangled in the law due to alleged blasphemy cases and the spread of false information when defending the Christian faith. This study aims to find the rule of law's cause and effect in blasphemy, provide insight into the purpose of apologetics, and explain how apologetics does not violate legal or religious norms. The method used in thisresearch is a qualitative method that prioritizes literature studies, collects data through scientific journals, and shares news on social media. The findings suggest that apologetics is a way of defending the faith when it is attacked by others, and it is an obligation for Christians. Apologetics is gentle, non-arrogant, and biblical. The maximum criminal penalty for blasphemy cases is ten years, and there is no equal legal protection between religious minorities and majorities in the application of the "Conditio Sine Qua Non Principle", so to defend it is enough to reveal the truth of God's Word without attacking other people's religions. ABSTRAKIde penulisan topik ini berawal dari pengamatan dimedia sosial ada  beberapa apologet Kristen terjerat hukum akibat dugaan kasus penodaan agama dan penyebaran informasi bohong saat melakukan pembelaan terhadap iman Kristiani. Penelitian ini bertujuan menemukan aturan hukum sebab akibat dalam penodaan agama, memberikan wawasan dan  tujuan apologetika, bagaimana apologetika yang tidak melanggar norma  hukum dan norma agama. Metode yang digunakan pada  penelitian ini adalah metode kualitatif dengan mengutamakan studi kepustakaan, melakukan pengumpulan data melalui jurnal ilmiah, berita di media sosial. Hasil temuan mengemukakan; apologetika adalah suatu cara pembelaan iman yang dilakukan ketika iman Kristen diserang oleh Pihak lain, dan ini merupakan kewajiban bagi orang Kristen. Apologetika dilakukan dengan  lemah lembut, tidak sombong dan Alkitabiah. Sanksi  pidana  maksimal dari kasus penodaan agama adalah sepuluh tahun, dan belum adanya perlindungan hukum yang sama  antara minoritas dan mayoritas beragama dalam penerapan “Asas Conditio Sine Qua Non”, sehingga untuk melakukan pembelaan cukup mengungkap kebenaran Firman Tuhan tanpa menyerang agama orang lain. Kata Kunci : Apologetika, Iman dan Rasa Adil